Identifying critical success factors (CSFs) of implementing building information modeling (BIM) in Malaysian construction industry - Yaakob, Mazri; Wan Ali, Wan Nur Athirah; Radzuan, Kamaruddin (2016)
Building Information Modeling (BIM) is defined as existing from the earliest concept to demolition and it involves creating and using an intelligent 3D model to inform and communicate project decisions.This research aims to identify the critical success factors (CSFs) of BIM implementation in Malaysian construction industry. A literature review was done to explore previous BIM studies on definitions and history of BIM, construction issues, application of BIM in construction projects as well as benefits of BIM. A series of interviews with multidisciplinary Malaysian construction experts will be conducted purposely for data collection process guided by the research design and methodology approach of this study.The analysis of qualitative data from the process will be combined with criteria identified in the literature review in order to identify the CSFs.Finally, the CSFs of BIM implementation will be validated by further Malaysian industrialists during a workshop. The validated CSFs can be used as a term of reference for both Malaysian practitioners and academics towards measuring BIM effectiveness level in their organizations.